Pulmonary Artery Denervation Reduces Pulmonary Artery Pressure and Induces Histological Changes in an Acute Porcine Model of Pulmonary Hypertension. (November 2015) - Rothman, Alexander M.K.; Arnold, Nadine D.; Chang, William; Watson, Oliver; Swift, Andrew J.; Condliffe, Robin; Elliot, Charlie A.; Kiely, David G.; Suvarna, S. Kim; Gunn, Julian; Lawrie, Allan
Abstract : Background—: Pulmonary arterial hypertension is a devastating disease with high morbidity and mortality and limited treatment options. Recent studies have shown that pulmonary artery denervation improves pulmonary hemodynamics in an experimental model and in an early clinical trial. We aimed to evaluate the nerve distribution around the pulmonary artery, to determine the effect of radiofrequency pulmonary artery denervation on acute pulmonary hypertension induced by vasoconstriction, and to demonstrate denervation of the pulmonary artery at a histological level. Methods and Results—: Histological evaluation identified a circumferential distribution of nerves around the proximal pulmonary arteries. Nerves were smaller in diameter, greater in number, and located in closer proximity to the luminal aspect of the pulmonary arterial wall beyond the pulmonary artery bifurcation. To determine the effect of pulmonary arterial denervation acute pulmonary hypertension was induced in 8 pigs by intravenous infusion of thromboxane A2 analogue. Animals were assigned to either pulmonary artery denervation, using a prototype radiofrequency catheter and generator, or a sham procedure. Pulmonary artery denervation resulted in reduced mean pulmonary artery pressure and pulmonary vascular resistance and increased cardiac output. Ablation lesions on the luminal surface of the pulmonary artery were accompanied by histological and biochemical alteration in adventitial nerves and correlated with improved hemodynamic parameters. Conclusions—: Pulmonary artery denervation offers the possibility of a new treatment option for patients with pulmonary arterial hypertension. Further work is required to determine the long-term efficacy and safety. Abstract : Supplemental Digital Content is available in the text.